Aridity modulates grassland biomass responses to combined drought and nutrient addition - Bondaruk, Viviana F. (2025)
Plant biomass tends to increase under nutrient addition and decrease under drought. Biotic and abiotic factors influence responses to both, making the combined impact of nutrient addition and drought difficult to predict. Using a globally distributed network of manipulative field experiments, we assessed grassland aboveground biomass response to both drought and increased nutrient availability at 26 sites across nine countries. Overall, drought reduced biomass by 19% and nutrient addition increased it by 24%, resulting in no net impact under combined drought and nutrient addition. Among the plant functional groups, only graminoids responded positively to nutrients during drought. However, these general responses depended on local conditions, especially aridity. Nutrient effects were stronger in arid grasslands and weaker in humid regions and nitrogen-rich soils, although nutrient addition alleviated drought effects the most in subhumid sites. Biomass responses were weaker with higher precipitation variability. Biomass increased more with increased nutrient availability and declined more with drought at high-diversity sites than at low-diversity sites. Our findings highlight the importance of local abiotic and biotic conditions in predicting grassland responses to anthropogenic nutrient and climate changes.